Extraction of Polysaccharides from Root of Pseudostellaria heterophylla (Miq.) Pax. and the Effects of Ultrasound Treatment on Its Properties and Antioxidant and Immune Activities - Hangyu Li; Ziwei Liu; Qianqian Liu; Xinnan Zhang; Sheng Li; Feng Tang; Linzi Zhang; Qian Yang; Qiran Wang; Shuyao Yang; Ling Huang; Yuwei Ba; et al. (Molecules, 2023)
The hydrophilic polysaccharides (PS) were isolated and purified from the tuberous roots of Pseudostellaria heterophylla. The extraction process of PS from Pesudostellariae radix was optimized by single–factor experiments and orthogonal design. The extract was purified by DEAE cellulose column to obtain the pure polysaccharide PHP. Then PHP was treated with different intensities of sonication to study the effect of sonication on PHP’s characteristics and its biological activity in vitro and in vivo. The results of this study revealed that ultrasound treatment did not significantly change the properties of PHP. Further, with the increase of ultrasound intensity, PHP enhanced the proliferation and phagocytosis of macrophage RAW264.7. Meanwhile, it could also significantly improve the body’s antioxidant activity and immune function. The results of this study demonstrated that PHP has the potential as a food additive with enhanced antioxidant and immune functions, and its biological activities could be enhanced by sonication.